2015
DOI: 10.1149/2.0021505jes
|View full text |Cite
|
Sign up to set email alerts
|

Towards Implantable Bio-Supercapacitors: Pseudocapacitance of Ruthenium Oxide Nanoparticles and Nanosheets in Acids, Buffered Solutions, and Bioelectrolytes

Abstract: Metal oxides, in particular ruthenium-based oxides, are promising electrode materials for aqueous pseudocapacitors. Strong acids or bases are favored over neutral electrolytes owing to the higher capacitance. Here we explore the pseudocapacitive behavior of ruthenium oxide nanoparticles and nanosheets in near neutral pH as an environmentally benign electrolyte. The pseudocapacitive charge storage in poorly-crystalline hydrous RuO 2 nanoparticles, and highly-crystalline RuO 2 nanosheets were investigated in ace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 33 publications
1
35
0
Order By: Relevance
“…Thus, the higher specific capacitance in the former is ascribed to enhanced pseudo‐capacitance, owing to the open‐framework morphology of the nanosheets that facilitates smooth penetration of ions into the porous channels ( Figure (c)). Moreover, de‐convolution of the total capacitance observed at different pH media reported highest specific capacitance in acidic electrolytes owing to maximum contribution from proton‐involved surface Faradaic processes which is less prominent in alkaline and neutral electrolyte (Figure (d)) …”
Section: Strategies For Improving Electrochemical Signatures In Ruo2 mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the higher specific capacitance in the former is ascribed to enhanced pseudo‐capacitance, owing to the open‐framework morphology of the nanosheets that facilitates smooth penetration of ions into the porous channels ( Figure (c)). Moreover, de‐convolution of the total capacitance observed at different pH media reported highest specific capacitance in acidic electrolytes owing to maximum contribution from proton‐involved surface Faradaic processes which is less prominent in alkaline and neutral electrolyte (Figure (d)) …”
Section: Strategies For Improving Electrochemical Signatures In Ruo2 mentioning
confidence: 99%
“…Moreover, de-convolution of the total capacitance observed at different pH media reported highest specific capacitance in acidic electrolytes owing to maximum contribution from proton-involved surface Faradaic processes which is less prominent in alkaline and neutral electrolyte ( Figure 9(d)). [108] Besides the above discussion related to tuning and optimization of aspect ratio, other important factors such as porosity, film thickness, texture and crystallite size, interconnected network structural aspects are equally important to optimize all the parameters leading to expected capacitance values.…”
Section: Strategies For Improving Electrochemical Signatures In Ruo 2mentioning
confidence: 99%
“…Yet pioneering advances are being already provided, for example, towards implantable bio-supercapacitors. [ 769 ] Another issue is the relatively low specifi c energy (high molecular weight and low working potentials) that can be stored in such biomolecular systems. However, interfacing such technologies with the human body to draw, store and deliver electrical energy when needed for example, to power a wearable electronic device, via a tattooed or skin integrated devices could be regarded now as a science fi ction vision although the potential and interest are massive.…”
Section: What's Next?mentioning
confidence: 99%
“…16 Further studies revealed that more environmentally benign electrolytes such as acetic acid-lithium acetate (AcOH-AcOLi) buffered solutions with near neutral pH (pH 5.8) could also be used as electrolytes affording high pseudocapacitance. 41,42 Astonishingly, the achievable maximum capacitance was actually higher for AcOH-AcOLi than H 2 SO 4 electrolyte with comparable rate performance. Bio-electrolytes such as phosphate buffered saline and fetal bovine serum also showed specific capacitance of 837 and 772 F g ¹1 , respectively, opening the possibility of using these electrode materials for safe and bio-compatible implantable power sources.…”
Section: Pseudocapacitive Charge Storage In Expandable (Water Swellabmentioning
confidence: 93%
“…Bio-electrolytes such as phosphate buffered saline and fetal bovine serum also showed specific capacitance of 837 and 772 F g ¹1 , respectively, opening the possibility of using these electrode materials for safe and bio-compatible implantable power sources. 42…”
Section: Pseudocapacitive Charge Storage In Expandable (Water Swellabmentioning
confidence: 99%